The Implementation and Volatility Analysis of Sharia Cryptocurrencies - Arifin, Syamsul; Yaqin, Abdullah; Syamsuddin, Syamsuddin; Zaenal Abidin, Muhammad (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2025)
This study analyzes the implementation of sharia-compliant cryptocurrencies and compares their volatility with Bitcoin and the Indonesia Stock Exchange Composite Index (IHSG). Using a mixed method approach with a sequential exploratory design, the research combines a literature review on sharia compliance and time-series analysis using the ARIMA model. The analysis focuses on two gold-backed cryptocurrencies, OneGram Coin (OGC) and GOLDX. Findings indicate that although OGC and GOLDX meet several key sharia criteria, such as asset backing, avoidance of maysir, gharar, and riba, supervision by a Sharia Supervisory Board, and the allocation of philanthropic funds (tabarru’), their volatility is higher than both Bitcoin and IHSG. This suggests that despite being designed for sharia compliance, these cryptocurrencies are currently less stable and less effective as a medium of exchange than their conventional counterparts. Additionally, the absence of government regulation and the lack of sharia-based profit-sharing models such as mudharabah or musyarakah remain significant shortcomings. The study recommends stronger collaboration between developers and regulators to improve regulatory frameworks and align sharia-based cryptocurrency systems with the principles of justice, stability, and sustainability as outlined in maqashid sharia.